Structural Stability in Models of American Trade Union Growth - Sheflin, Neil; Troy, Leo; Koeller, C. Timothy (Quarterly Journal of Economics, 1981)
Recent interest in trade union activity has led to the development of econometric models of union membership growth. This paper examines the structural stability of two of the leading models—Ashenfelter-Pencavel's and Bain-Elsheikh's—each of which claimed to have captured the primary determinants of union growth in the twentieth century. The models were reestimated using revised, corrected, and extended membership data, and a nonlinear, maximum-likelihood procedure was employed to estimate the shift-point for each model. Contrary to previous studies, we found evidence of a break in the structure of each model. And unlike earlier work that hypothesized a World War II break-point, our estimated point was 1937–1938, most likely reflecting the impact of the Wagner Act.